2011
DOI: 10.1097/jto.0b013e31820517a3
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Thoracic Cytology for New Therapeutic Paradigms in Non-small Cell Lung Carcinoma: High Accuracy of Tumor Subtyping and Feasibility of EGFR and KRAS Molecular Testing

Abstract: Cytologic subtyping of NSCLC is feasible and accurate, particularly when morphologic assessment is combined with IHC. Furthermore, routine cytologic specimens can be successfully used for EGFR/KRAS mutation analysis. Our data strongly support the suitability of cytologic specimens for the new therapeutic paradigms in NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
253
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 226 publications
(275 citation statements)
references
References 40 publications
(42 reference statements)
15
253
2
5
Order By: Relevance
“…Therefore the optimal assessment of accuracy may in fact be consensus among multiple pathologists. While some experts have suggested that cytology smears may provide greater nuclear and cytoplasmic resolution than histology [25], our results suggest that this is most likely to be achieved through H&E examination and use of IHC staining, rather than simply relying on a smear diagnosis.…”
Section: Limitationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore the optimal assessment of accuracy may in fact be consensus among multiple pathologists. While some experts have suggested that cytology smears may provide greater nuclear and cytoplasmic resolution than histology [25], our results suggest that this is most likely to be achieved through H&E examination and use of IHC staining, rather than simply relying on a smear diagnosis.…”
Section: Limitationsmentioning
confidence: 79%
“…The proportion of NOS as the histologic diagnosis in NSCLC has increased over time, which may be due to increasing use of minimally invasive means to achieve diagnosis [24]. Smallvolume specimens may be paucicellular or have an absence of tissue architecture, making identification of tumour subtype more difficult [25]. Use of IHC stains may potentially overcome …”
Section: Discussionmentioning
confidence: 99%
“…In addition, it remains unclear which procedural techniques are superior to others for diagnosis and molecular testing. Although core biopsies have traditionally been thought to be superior to cytological specimens, recent data suggest a 98% success rate for EGFR and KRAS testing on pure cytological specimens with the capability to make a tissue block from fine needle aspirations (FNAs) and thoracentesis [29]. Consequently, decisions related to initial tissue acquisition often involve weighing the risks of performing an invasive procedure more likely to yield adequate tissue versus a less invasive procedure that may be easier and pose less risk for the patient.…”
Section: Challenge: Optimizing Tissue Acquisition and Processingmentioning
confidence: 99%
“…Several studies have shown that cytological specimens obtained by EBUS-TBNA are suitable for molecular testing for EGFR, Kirsten rat sarcoma viral oncogene homolog (K-ras), and ALK status (14)(15)(16)(17). Optimal use of EBUS-TBNA for lung cancer diagnosis and staging requires a coordinated effort between the bronchoscopist and the cytopathologist to collect and triage specimens for diagnostic testing.…”
Section: Early and Specific Diagnosismentioning
confidence: 99%